The County Emergency Manager's Role in Recovery. Issue 1 (March 2014) - Jensen, Jessica; Bundy, Sarah; Thomas, Brian; Yakubu, Mariama
For decades emergency management has presented itself as an emerging profession devoted to coordinating activities related to mitigation, preparedness, response, and recovery. However, there has been little research to assess the extent to which it is, in fact, engaged in the coordination of activities in all of these areas. This study addresses this research gap by reporting the results of interviews with 54 county level emergency managers from eleven states regarding their role in disaster recovery. The results suggest that recovery is subordinate to other functional areas (e.g., preparedness, response, mitigation) within the work lives of the county emergency managers who participated in this research.